Factors associated with deficiencies in packaging of surgical instrument by staff at a single center in China - Yanhua Chen; Liangying Yi; Juan Hu; Ruixue Hu (BMC Health Services Research, 2022)
Abstract Background Surgical instrument packaging quality directly affects the safety and performance of surgery. We aimed to investigate the factors causing defects in surgical instrument packaging and recommend strategies to prevent defects in surgical instrument packaging. Methods We collected surgical instrument packaging data regarding age, gender, length of service, educational background, number of staff dealing with packaging, time period of packaging, instrument specification, where the wrap was intact, whether the wrap reached the required quality of cleaning, and whether the instruments were satisfactorily cleaned in compliance with guidelines from 5000 surgical instrument packages during June-December 2018 at Central Sterile Supply Department of the West China Second University Hospital, Sichuan University. Meanwhile, a questionnaire survey completed by the operating room staff using surgical instruments was used to measure the level of their satisfaction with the instruments in the packages. We utilized single-factor analysis to investigate possible factors that might cause defects in surgical instrument packaging, and conducted multivariate logistic regression analysis of the factors associated with defects in packaging. Results Length of service, educational background, number of staff dealing with packaging, time period of packaging, instrument structure, whether the wrap was intact, whether the wrap reached the required quality of cleaning, and whether the surgical instruments were satisfactorily cleaned in compliance with guidelines were the factors significantly (P < 0.05) associated with defects in surgical instrument packaging. Conclusion This study reveals that various factors are associated with defects in surgical instrument packaging. Recommendations for reducing incidences of defects include improved scheduling of packaging workload, greater provision of training in packaging skills, and standardization of packaging procedure.